Diagnosis and Management of Filler Adverse Effects: An Algorithm - Feller-Heppt, Gabriele; Haneke, Eckart; Heppt, Markus V. (Facial Plastic Surgery, 2014)
Fillers are frequently used in beautifying procedures. Despite major advancements of the chemical and biological features of injected materials, filler-related adverse events may occur, and can substantially impact the clinical outcome. Filler granulomas become manifest as visible grains, nodules, or papules around the site of the primary injection. Early recognition and proper treatment of filler-related complications is important because effective treatment options are available. In this report, we provide a comprehensive overview of the differential diagnosis and diagnostics and develop an algorithm of successful therapy regimens.
Keywords: injectable fillers; side effects; granuloma; differential diagnosis; treatment